Sosialisasi Pemanfaatan Media Pembelajaran Berbasis Audio Visual Dalam Pembelajaran Fiqih Thaharah SD Islam Darul Athfal Tanjung Seneng - yunianto, Teguh; Khumaidi, Muhammad Wisnu (STIT Darul Fattah Bandar Lampung, 2024)
The purpose of this community service activity is to improve students' understanding of the material of fiqh thaharah by using audio-visual media, so that teachers can be more creative in delivering the material to students. The classical approach is carried out when providing theories about the development of correct learning media and the individual approach is carried out when practicing making learning media. The method used in this activity is socialization by conducting various lectures, demonstrations, and tests. Data collection techniques in the form of observation and tests to determine whether or not this socialization is necessary. The results of the implementation of this activity are in accordance with the targets planned at the beginning, namely that the participants of the socialization have been able to understand the material of fiqh thaharah according to what was taught and they are able to apply the material presented well